Seleksi Dan Identifikasi Lactobacillus Kandidat Probiotik Penurun Kolesterol Berdasarkan Analisis Sekuen 16s Rna - Evi Triana; Novik Nurhidayat (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
High fat and low fiber dietary pattern results in raising of blood cholesterol level over the normal level, namely hypercholesterolemia. Hypercholesterolemia might cause coronary disease and stroke. Blood cholesterol is able to be decreased by probiotic supplement. Lactobacillus is one of the probiotics that were well known and taken advantages. However its role as cholesterol lowering agent was less known. Therefore, screening and identification of Lactobacillus isolates which were candidates of probiotic have been carried out. Isolates Mar 8, Lac 3 and 7 p have been selected as Lactobacillus candidates for cholesterol lowering probiotic. Those isolates met criteria for cholesterol lowering probiotics. Furthermore, they have been conducted to confirm their identity as Lactobacillus. 16S RNA sequences analysis by BLAST analysis against reference strains within DNA Data Bank of Japan (DDBJ) have been carried on. Results showed that sequences of Lactobacillus Mar 8 was 100% homology with Lactobacillus plantarum, Lac 3 was 100% homology with Lactobacillus paracasei and 7 p was 99% homology with Lactobacillus plantarum. It was concluded that the three isolates were selected as candidates for cholesterol lowering probiotics. Both of them, Mar 8 and 7 p, are Lactobacillus plantarum. Another one, Lac 3 is Lactobacillus paracasei.